New Modification of Natural Coagulants and Flocculants from Papaya Seeds (Carica Papaya L.) and Aloe Vera Gel in The Removal of Remazol Yellow Dye - Wijaya, Khalida; Fardiyah, Qonitah; Rumhayati, Barlah (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2025)
A new modification of natural coagulant and flocculant from papaya seeds Carica papaya L. and aloe vera gel has been developed in this study to remove Remazol Yellow dye. The research parameters studied included the initial concentration of the test solution, pH, and stirring speed during the coagulation process. The initial concentration of the test solution varied from 10 to 50 mg/L, the pH ranged from 1 to 6, and the stirring speed was 650 to 1050 rpm during the coagulation phase. The coagulation and flocculation results were characterized using an FTIR spectrophotometer. The results showed that the optimum conditions were an initial concentration of 30 mg/L at pH 2 and a stirring speed of 950 rpm, resulting in the highest removal effectiveness of 97.55%. The results of FTIR spectrophotometry characterization showed that the sulfonate group -SO₃⁻ in Remazol Yellow had been removed, indicating that the protonated groups -NH₃⁺ and -COOH₂⁺ in papaya seeds and the anionic groups of the dye had electrostatic interactions. This study shows that the modification of papaya seeds and aloe vera gel as natural coagulants and flocculants shows sustainable potential for azo dye-based textile wastewater treatment.